2000
DOI: 10.1084/jem.192.12.1819
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Inert HIV-Specific Cytotoxic T Lymphocytes Do Not Play a Major Role in Chronically Infected Adults and Children

Abstract: The highly sensitive quantitation of virus-specific CD8+ T cells using major histocompatibility complex–peptide tetramer assays has revealed higher levels of cytotoxic T lymphocytes (CTLs) in acute and chronic virus infections than were recognized previously. However, studies in lymphocytic choriomeningitis virus infection have shown that tetramer assays may include measurement of a substantial number of tetramer-binding cells that are functionally inert. Such phenotypically silent CTLs, which lack cytolytic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 52 publications
(79 reference statements)
10
85
0
Order By: Relevance
“…The T cells from the ES have normal proliferative capacities, as they are derived from immunocompetent HIV-1-uninfected subjects (10,50). Thus, in ES, the ability to detect very low frequency responses may be greater in the CTL precursor analysis than the ex vivo ELISPOT analysis, in contrast to more recent studies comparing these assays in HIV-1-infected individuals (51)(52)(53). Protocols measuring cytolytic activities may also be less prone to identifying weak cross-reactivities, because T cells have to pass two check points for specificity, one during initial stimulation and a second during lysis of target cells.…”
Section: Discussionmentioning
confidence: 60%
“…The T cells from the ES have normal proliferative capacities, as they are derived from immunocompetent HIV-1-uninfected subjects (10,50). Thus, in ES, the ability to detect very low frequency responses may be greater in the CTL precursor analysis than the ex vivo ELISPOT analysis, in contrast to more recent studies comparing these assays in HIV-1-infected individuals (51)(52)(53). Protocols measuring cytolytic activities may also be less prone to identifying weak cross-reactivities, because T cells have to pass two check points for specificity, one during initial stimulation and a second during lysis of target cells.…”
Section: Discussionmentioning
confidence: 60%
“…One study of HIV infection found that Ag-specific CD8 ϩ T showed normal profiles of IFN-␥ production (48). However, there is other evidence that HIV-specific CD8 ϩ T cells may be functionally defective (49).…”
Section: Discussionmentioning
confidence: 99%
“…Tetramer staining of PBMC and disaggregated lymph node cells PBMC and disaggregated lymph node cells were stained with selected tetramers loaded with CD8 ϩ T cell HIV-1 epitopic peptides ( Table I) that matched subjects' HLA class I molecules. Tetramers were selected for analysis based upon prior reports in the literature (21)(22)(23)(24)(25) as well as unpublished experience within our laboratories that suggested there was a high likelihood for HIV-1-infected individuals to harbor such cells. Tetramers were obtained from the National Institute of Allergy and Infectious Diseases (NIAID) Tetramer Facility (Emory University, Atlanta, GA), except for those restricted by HLA-A*0201, which were purchased from Beckman Coulter.…”
Section: Frequencies Of Cd4mentioning
confidence: 99%